2012
DOI: 10.1371/journal.pmed.1001307
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Utility-Based Quality of Life in Chronic Kidney Disease Treatments

Abstract: Melanie Wyld and colleagues examined previously published studies to assess pooled utility-based quality of life of the various treatments for chronic kidney disease. They conclude that the highest utility was for kidney transplants, with home-based automated peritoneal dialysis being second.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
332
3
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 417 publications
(356 citation statements)
references
References 23 publications
13
332
3
8
Order By: Relevance
“…Astellas reports the findings of Wyld et al, 406 which does report utilities, deriving a disutility of 0.10 between 'no diabetes' and 'diabetes' groups of people with CKD. However, this is not restricted to only renal transplant population and it is not clear which utility elicitation method is used.…”
Section: Disutility Due To Diabetes Mellitusmentioning
confidence: 93%
“…Astellas reports the findings of Wyld et al, 406 which does report utilities, deriving a disutility of 0.10 between 'no diabetes' and 'diabetes' groups of people with CKD. However, this is not restricted to only renal transplant population and it is not clear which utility elicitation method is used.…”
Section: Disutility Due To Diabetes Mellitusmentioning
confidence: 93%
“…That is why patients treated with hemodialysis not only have a low health related quality of life as [35] as well as eexperienced mortality rates of 15%-20% each year [36].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Wyld et al [40] reported that PD resulted in a clinically higher QOL than HD, however, but the difference was not statistically significant. Hashimoto et al [9] found that QOL was improved among six patients switching from PD alone to combined therapy.…”
Section: Combined Therapy and Quality Of Lifementioning
confidence: 98%